2018
DOI: 10.2217/ije-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Adult-Type Granulosa Cell Tumor: Focusing on Endocrine-Based Therapies

Abstract: FOXL2 mutation is diagnostic, and, if pathology is in doubt, it should be performed.• Surgical resection and staging is key to assess prognosis.• Platinum-based adjuvant chemotherapy such as with carboplatin plus paclitaxel is a reasonable step for women diagnosed with distant recurrences or poor prognostic initial features. However, evidence for improved outcome is lacking. • Hormone-based therapies, especially with aromatase inhibitors, have shown activity and future studies may lead to further insight on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Estrogen-targeting therapies have shown marked promise in the treatment of GCTs [ 87 ]. In early studies prior to the use of aromatase inhibitors, tamoxifen produced a response rate (8%) and stable disease rate (32%) comparable to those obtained with epithelial ovarian cancer subtypes [ 87 ]. However, it is the aromatase inhibitors that are of great interest here.…”
Section: Targeting Er With Anti-estrogens and Aromatase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen-targeting therapies have shown marked promise in the treatment of GCTs [ 87 ]. In early studies prior to the use of aromatase inhibitors, tamoxifen produced a response rate (8%) and stable disease rate (32%) comparable to those obtained with epithelial ovarian cancer subtypes [ 87 ]. However, it is the aromatase inhibitors that are of great interest here.…”
Section: Targeting Er With Anti-estrogens and Aromatase Inhibitorsmentioning
confidence: 99%
“…However, it is the aromatase inhibitors that are of great interest here. As mentioned above, one of the consequences of the FOXL2 mutation is an increase in aromatase activity in malignant granulosa cells, and this, leads through an undefined mechanism, to sensitivity to aromatase inhibitors [ 87 ]. In a review summarizing the use of the aromatase inhibitors as single agents, 25 cases with known outcomes are described.…”
Section: Targeting Er With Anti-estrogens and Aromatase Inhibitorsmentioning
confidence: 99%
“…A more recent review in 2018 provided an updated meta-analysis including 12 different combinations of non-AI hormonal therapies (including GnRH agonists/antagonists, tamoxifen, progesterone, and diethylstilbestrol-DES), among 50 patients. The pooled analysis found clinical benefit for 33 of 50 patients and at least partial response in 17 patients [143]. The same review also compiled data for AI specifically, including letrozole, anastrozole, and exemestane.…”
Section: Endocrine Therapymentioning
confidence: 96%
“…In this data set of 25 patients, 7 experienced complete response, 5-partial response, and 7-disease stability for a total of 19 patients with clinical benefit. Given the favorable side effect profile, the authors concluded that AI may be an alternative to chemotherapy [143].…”
Section: Endocrine Therapymentioning
confidence: 99%
See 1 more Smart Citation